On Farm Testing of Chickpea (Cicer arietinum L.) Cultivars for Site-specific Assessment under Rainfed Condition of Western Rajasthan (Indian Journal of Extension Education, 2012)
To study the comparative performance of newly released as well as conventionally grown popular early, timely and late sown chickpea varieties, ten ’On Farm Assessment Trials (OFAT)’ were conducted during Rabi 2008-09, 2009-10 and 2010-11 at various locations in arid region Pali district of Rajasthan. Results of ’OFAT’ revealed that chickpea varieties viz. RSG-888 as well as RSG-991 were equally good performers under early sown conditions with respective average grain yields of 16.9 and 15.5 q/ha under rainfed. The variety GNG-1581 was tested under irrigated conditions and higher yield. Timely sown chickpea grown under rainfed conditions of Sumerpur, Raipur and Sojat blocks, RSG-896, GNG 1488, GNG-1292 and RSG-902 recorded grain yield ranging between 16.9 to 19.7 q/ha, while under irrigated conditions of Jaitaran and Sumerpur blocks, RSG-895, CSZD-884, Pratap-1 and RSG-807 performed better in terms of productivity and profitability with average grain yield ranging between 16.5 to 18.2 q/ha with highest yield in CSZD-884. The results under late sown rainfed chickpea indicated that GNG-469, GNG-663 and GNG-1958 recorded higher productivity over deshi chana, while new cultivars GNG-1969 was low performers under irrigated late sown conditions in terms of productivity and profitability over conventionally grown popular varieties GNG-469 and GNG-1958, respectively.